Graphene/zinc oxide nanocomposite : a versatile platform for electrochemical-based genosensor - Low, Sze Shin (2018)
In this work, a versatile electrochemical biosensing platform was developed based on graphene/zinc oxide (G/ZnO) nanocomposite. For the synthesis of G/ZnO nanocomposite, two facile and green approaches were employed to eradicate the issues associated with conventional methods, which use harsh chemicals and high temperature. The G/ZnO nanocomposite synthesised via low temperature hydrothermal growth method exhibited approximate 58 times improvement in terms of sensitivity as compared to the G/ZnO nanocomposite synthesised via the mechanical stirring method. Therefore, the G/ZnO nanocomposite with higher sensitivity was employed for the following work. Results from cyclic voltammetry and amperometry showed that the G/ZnO-modified electrode displayed a wide linear range up to 15 mM for the detection of H2O2 and sensitivity improvements of 200% in comparison to the control sample. Subsequently, an electrochemical genosensor based on G/ZnO nanocomposite was fabricated for the detection of Avian Influenza H5N1 virus. The G/ZnO-based genosensor displayed its potential in replacing the conventional detection method, with result showing higher sensitivity and efficiency. The G/ZnO-based genosensor was further applied for the detection of Coconut Cadang-Cadang Viroid disease (CCCVd) single stranded RNA (ssRNA). Promising results were obtained with high specificity in discriminating the target from mismatched ssRNA sequences.